The ant's panic - Khan, Saniyasnain (Goodword Kidz New Delhi, 2006)
The Ant's Panic is a whimsical tale that follows a little ant as it navigates a chaotic day, highlighting themes of teamwork, problem-solving, and the importance of staying calm in the face of unexpected challenges.